Effect of severity of urinary incontinence on quality of life in women - Krhut, Jan; Gärtner, Marcel; Mokris, Jan; Horcicka, Lukas; Svabik, Kamil; Zachoval, Roman; Martan, Alois; Zvara, Peter (Neurourology and urodynamics, 2018)
AIMS: While the effect of different types of incontinence on the quality of life (QoL) has been clearly documented, the information about the impact of incontinence severity on QoL in women is lacking. Therefore, we investigated whether increasingly severe degrees of incontinence were linearly correlated with poorer QoL. METHODS: We included 391 incontinent women and 81 continent volunteers in the study and assessed them in accordance with routine clinical practice. A 24 h pad-weight test was used to objectively quantify the incontinence severity. We then stratified participants according to incontinence type and severity and assessed correlations between incontinence severity and Patient Perception of Bladder Condition (PPBC), International Consultation on Incontinence short-form questionnaire (ICIQ-SF), and King's Health Questionnaire (KHQ) quality of life scores in the entire study population and in individual groups according to incontinence type. RESULTS: Minimal incontinence was associated with significant negative impact on QoL, as measured by all quality of life assement tools. There were nonlinear correlations between scores on individual questionnaires and daily leakage volumes. Stress urinary incontinence had a weaker impact on quality of life than urge or mixed incontinence, as measured by PPBC (P < 0.0001), KHQ part 1 (P < 0.0001), and KHQ part 2 (P < 0.001). Stress urinary incontinence also had a weaker impact on QoL than mixed incontinence as measured by ICI-Q (P = 0.007). CONCLUSIONS: This study demonstrated that even mild urinary leakage significantly reduces the QoL, while subsequent increase in the degree of incontinence has only minimal additional effect. There was no linear correlation between incontinence severity and QoL.
Keywords: Surveys and Questionnaires; vložky pro inkontinentní pacienty; Humans; Healthy Volunteers; lidé středního věku; nelineární dynamika; Quality of Life; Female; Aged; dospělí; senioři; lidé; inkontinence moči; kvalita života; Urinary Incontinence, Stress; průzkumy a dotazníky; Urinary Incontinence; Adult; stresová inkontinence moči; Urinary Incontinence, Urge; ženské pohlaví; Incontinence Pads; Middle Aged; urgentní inkontinence; Czech Republic; zdraví dobrovolníci pro lékařské studie; Česká republika; Nonlinear Dynamics